PETRAS GRISHKEVICIUS’ PERSONAL NETWORK: BETWEEN CLAN AND CONSOLIDATION OF NOMENKLATURA? - Grybkauskas, Saulius (Politologija, 2015)
The notion of a clan of the first secretary in the soviet Lithuania or, in contrast, speaking about the consolidated titular nomenklatura enables to penetrate deeply into the governing of a soviet republic. The key questions here are: what kind of networks? Could the sort of networks and trust help us explain political dynamics in the soviet Lithuania and reasons why exactly Soviet Lithuanian Communist party became the first one in the Soviet Union that break with CPSU in 1989? What kind of circumstances and political context made possible the horizontal links among nomenklatura members and made nomenklatura likely to be a more consolidated network than the personal clan of the first secretary in such a centralized soviet system?Seeking to draw a difference between the clan and the consolidated titular nomenklatura, useful is the concept of krugavaya poruka presenting the Lithuanian nomenklatura as a cycle of functionaries bounded with interpersonal ties and collective responsibility against Moscow to drain out the political forms of nationalism in society. This article focuses on the personal network of Petras Griškevičius, the first secretary of the Communist party of Lithuania (1974–1987), revealing the importance of his networking in controlling the soviet Lithuanian nomenklatura.Griškevičius’ leadership network consisted of professionals and technocrats (functional nomenklatura), on the one hand, and the functionaries loyal to Griškevičius personally (Griškevičius’ personal clan) on the other. Tensions between members of functional nomenklatura and representatives of his personal clan appeared in many sectors of political, economic and social life of the republic. The article investigates cases of intelligentsia and technocracy in order to show how Griškevičius had used the competition between the functional nomenklatura and members of his personal clan aiming to gain more power.While the first secretary succeed in keeping balance among nomenklatura members, his power was limited by political circumstances. There were at least three factors that made possible the distinguished situation in the soviet Lithuania: 1) high expression of nationalism in society, 2) low status of the first secretary of the republic’s Communist party, 3) the role of the second secretary of the Communist party sent by Moscow into republic’s leadership.The obligation against Moscow to drain out political forms of nationalism in the republic led to functionalism in its nomenklatura leadership. Threat and political responsibility for the expression of nationalism demanded functional skills from party and soviet managers able to deal with political, social, and economic problems in the republic. For this reason, Griškevičius could not behave in the nepotism way by recruiting only trusted and personally loyal to him functionaries into leadership; he needed professionals.Secondly, in contrast to the “masters” in other republics, the first secretary of the soviet Lithuania had a comparatively low status in all-Union institutions. Both the first and second secretaries were only a member and a candidate member of the Central Committee of the CPSU. This low status of the first secretary in all-Union bureaucracy ranking made an impact on the behavior of the local nomenklatura, because it got a room for the personal play between the first and the second secretaries.